1998
DOI: 10.1002/pro.5560070118
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the heteromeric transcriptional activator MvaT of the Pseudomonas mevalonii mvaAB operon

Abstract: The mvaAB operon of Pseudomonas mevalonii encodes HMG-CoA reductase (EC 1.1.1.88) and HMG-CoA lyase (EC 4.1.3.4), enzymes that catalyze the initial reactions of mevalonate catabolism in this organism. Expression of this operon is regulated by the constitutively expressed transcriptional activator protein MvaT that binds in vitro to an upstream regulatory element. Mevalonate is essential for activation of transcription in vivo, and in vitro data demonstrated that MvaT binds to the rnvaAB cis-regulatory element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
(16 reference statements)
0
26
0
2
Order By: Relevance
“…The comparison of the Pseudomonas strain On: Fri, 11 May 2018 05:53:00 Y1000 H-NS-like protein amino acid sequence with all sequences present in databases revealed approximately 50 % identity with MvaT, a transcriptional activator that participates in the control of mevalonate metabolism in Pseudomonas mevalonii (Rosenthal et al, 1998). By scanning complete and unfinished bacterial genome sequences, we identified at least one homologous protein in each Pseudomonas species.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The comparison of the Pseudomonas strain On: Fri, 11 May 2018 05:53:00 Y1000 H-NS-like protein amino acid sequence with all sequences present in databases revealed approximately 50 % identity with MvaT, a transcriptional activator that participates in the control of mevalonate metabolism in Pseudomonas mevalonii (Rosenthal et al, 1998). By scanning complete and unfinished bacterial genome sequences, we identified at least one homologous protein in each Pseudomonas species.…”
mentioning
confidence: 95%
“…All these proteins display at least 47 % amino acid identity. Except for the MvaT proteins of P. mevalonii and P. aeruginosa, which possess a regulatory role in mevalonate metabolism and in virulence gene expression, respectively (Rosenthal et al, 1998;Diggle et al, 2002), the function of the Pseudomonas H-NS-related proteins remains unknown and some have been annotated as hypothetical proteins. Overexpression of the hns-like gene of Pseudomonas strain Y1000 in the same strain from the low-copy-number vector pDIA584, i.e.…”
mentioning
confidence: 99%
“…2a). A search of the P. aeruginosa genome with the amino acid sequences obtained from amino terminus sequencing showed that the 9 kDa protein is the P. aeruginosa HU protein, which is encoded by the hupB gene (Delic-Attree et al, 1995), while the 16 kDa protein is the P. aeruginosa transcriptional regulator MvaT (Diggle et al, 2002), a homologue of the MvaT beta subunit in Pseudomonas mevalonii (Rosenthal & Rodwell, 1998). Three other column fractions produced gel shift bands that varied in their migration distance when compared to the 0?6 M KCl fraction (data not shown).…”
Section: Enrichment and Identification Of The Dna-binding Proteinsmentioning
confidence: 99%
“…Identification and in Silico Analysis of TurA Protein-The amino acid sequence of P16 amino-terminal end was determined, searched through the KT2440 deduced protein data base at The Institute for Genomic Research (TIGR) Comprehensive Microbial Resource (31,32), and found at the aminoterminal of a small deduced protein of 125 amino acids, accession number PP1366, annotated as sharing a high degree of similarity with the transcriptional regulator MvaT, P16 subunit (33). Standard BLAST search (34) also found in KT2440 genome four open reading frames (loci PP3765, PP0017, PP3693, PP2947, respectively) that code for protein paralogues of P16.…”
Section: Screening For Novel Regulatory Proteins Of the Host Strain Pmentioning
confidence: 99%